Preliminary using the lectin from maritima jackbean seeds (Canavalia maritima Aublet) for analysis of IgG from human serum by Lectin-Elisa technique - Lien, Tran Thi Phuong; Chau, Truong Van; Phuc, Do Van; Lien, Do Ngoc (Academia Journal of Biology, 2012)
In recent investigation, we proved specific interaction between lectin ConM from Canavalia maritima of Vietnam and IgG from human serum. In order to using the lectin for analysis IgG from human serum, we carried out the purification of IgG from healthy human serum by Protein A - Sepharose 4B and ConM-Sepharose 4B column chromatography followed to prepare the ConM-ELISA biokit for analyzing IgG from human serum. Results obtained showed that average concentration of IgG from healthy human serum was determined to be 12.7 mg/ml. Using suitable concentration of ConM to be 5 mg/well by ConM-ELISA technique with human serum diluted 200 times.